DPP-4 inhibitor and estrogen share similar efficacy against cardiac ischemic-reperfusion injury in obese-insulin resistant and estrogen-deprived female rats - Sivasinprasasn S. (2017)
© The Author(s) 2017. Estrogen deprivation aggravates cardiac injury after myocardial ischemia and reperfusion (I/R) injury. Although either estrogen or the dipeptidyl peptidase-4 (DPP-4) inhibitor, vildagliptin, reduces myocardial damage following cardiac I/R, their effects on the heart in obese-insulin resistant and estrogen deprived conditions remain unknown. Ovariectomized (O) rats (n = 36) were divided to receive either normal diet (NDO) or high-fat diet (HFO) for 12 weeks, followed by treatment with a vehicle, estrogen or vildagliptin for 4 weeks. The setting of in vivo cardiac I/R injury, 30-min ischemia and 120-min reperfusion, was performed. At 12 weeks after ovariectomy, both NDO and HFO rats exhibited an obese-insulin resistant condition. Both NDO and HFO rats treated with estrogen and vildagliptin showed reduced fasting plasma glucose, insulin and HOMA index. Both treatments improved cardiac function indicated by restoration of heart rate variability and increased %left ventricular ejection fraction (%LVEF). The treatments similarly protected cardiac mitochondrial function against I/R injury, leading to a reduction in the infarct size, oxidative stress and apoptosis in the ischemic myocardium. These findings demonstrate that vildagliptin effectively improves metabolic status, and shares similar efficacy to estrogen in reducing myocardial infarction and protecting cardiac mitochondrial function against I/R injury in estrogen-deprived obese-insulin resistant rats.